정상 아동과 성대 결절 아동의 음성 오용 및 남용 행동의 발생 빈도 비교 - 이무경(Moo-Kyung Lee) (한국콘텐츠학회 논문지, 11(9), 2011)
There have been several studies reporting that vocal misuse and abuse causes voice problems, as well as laryngeal disease such as laryngitis, vocal nodules, vocal polyp. But few researches have investigated amounts or rates of vocal misuse or vocal abuse of patients. Therefore, the author of this study developed measuring device for vocal misuse and abuse behaviors and compared frequency of vocal misuse and abuse behaviors of normal children and children with vocal nodules. The subjects of this study were five normal children and five children with vocal nodules who were male, lower graders of elementary schools(first to third graders). Based on the results of this study, the frequency of the children with vocal nodules in vocal misuse and abuse using was 5,411(${±}145$) and that of the normal children was 3,133(${±}257$). The frequency of vocal misuse and abuse behaviors of the children with vocal nodules was around 1.5 time significantly higher than that of normal children(p<.001). 음성 오용이나 남용이 후두염, 성대 결절, 성대 폴립 등과 같은 후두 질환 뿐 아니라 음성 문제의 원인이 된다는 사실을 여러 문헌들에서 밝히고 있지만 음성 환자들이 음성을 오 남용하는 양이나 비율에 관해서 이루어진 연구는 매우 부족하다. 본 연구는 성대 결절 환자의 이러한 음성 오 남용 비율을 측정하기 위하여 연구 목적에 부합하는 실험 도구를 개발하였고, 정상 아동과 성대 결절 아동의 음성 오 남용 행동의 발생 빈도를 정량적으로 비교하였다. 실험은 초등학교 저학년(1학년~3학년) 남자 아동 가운데, 정상 아동 5명과 성대 결절 아동 5명을 대상으로 하였다. 연구 결과, 성대 결절 아동의 음성 오.남용 빈도수는 평균 5,411(${±}145$)회, 정상 아동은 평균 3,133(${±}257$)회였으며, 성대 결절 아동이 정상 아동 집단 보다 음성 오 남용 행동의 발생 빈도수가 1.5배 정도 유의하게 높은 것으로 나타났다(p<.001).